The Validity of the Guided Inquiry-Based Teaching Module on Additives to Improve Students' Scientific Attitudes - Alfin, Muhammad Babun; Cahyono, Edy; Ridlo, Saiful; Sumarni, Woro; Widiyatmoko, Arif (Universitas Negeri Semarang, 2024)
The Ministry of Education, Culture, Research, and Technology fostered the Merdeka Curriculum program as a significant endeavor to recuperate from the academic situation after the COVID-19 outbreak. The Merdeka Curriculum has shown better results two years after the pandemic than in the previous academic years. It indicates that learning will be more significant if students independently find ideas through the logical cycle since this can create and bring about scientific attitudes. This research aims to analyze the validity of the guided inquiry-based teaching module on additives to improve students' scientific attitudes. This is an R&D study adopting the 4D model and restricted to the development stage. Questionnaires were used as the instrument for the data collection. The validation included media and content validity, carried out by respectively 1 lecturer as a media specialist and 1 lecturer as a content specialist. The validation results revealed that the developed teaching module obtained 0.95 with very valid criteria from the media specialist and 0.96 with very valid criteria from the content specialist. In sum, the developed teaching module is valid for use in the learning process.